2(3x+4)=-5(5x-3)

Simple and best practice solution for 2(3x+4)=-5(5x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+4)=-5(5x-3) equation:


Simplifying
2(3x + 4) = -5(5x + -3)

Reorder the terms:
2(4 + 3x) = -5(5x + -3)
(4 * 2 + 3x * 2) = -5(5x + -3)
(8 + 6x) = -5(5x + -3)

Reorder the terms:
8 + 6x = -5(-3 + 5x)
8 + 6x = (-3 * -5 + 5x * -5)
8 + 6x = (15 + -25x)

Solving
8 + 6x = 15 + -25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '25x' to each side of the equation.
8 + 6x + 25x = 15 + -25x + 25x

Combine like terms: 6x + 25x = 31x
8 + 31x = 15 + -25x + 25x

Combine like terms: -25x + 25x = 0
8 + 31x = 15 + 0
8 + 31x = 15

Add '-8' to each side of the equation.
8 + -8 + 31x = 15 + -8

Combine like terms: 8 + -8 = 0
0 + 31x = 15 + -8
31x = 15 + -8

Combine like terms: 15 + -8 = 7
31x = 7

Divide each side by '31'.
x = 0.2258064516

Simplifying
x = 0.2258064516

See similar equations:

| -19-5x=-17x+17 | | 17x+x=-4x | | 7x-7=13+12y | | 17r+18=221-12r | | x^2+0x-1=01 | | y-5=6(x+4) | | -2.4(-2p+2)+0.5p= | | 14+Y=49 | | 3(4x-8)=31-4(x+2) | | 2w+18-3w-5=18 | | 21-9f=(-20f-6) | | 4v+16=56-v | | 4x^2-54x+110=0 | | 18n-6=19n-8 | | 49v+7=4v-18+70 | | 7r-16=2r-1 | | 10p-3=2p+21 | | x-3-6x=-3x-7+5x | | (3x-2)(3x-2)=15 | | 4y^2+9u+2=0 | | 7x+8=x+32 | | 14y+16=48-15+18 | | 3/8(x-4)=24 | | y=17+-7x | | y=x^2+7x-2 | | -8xy+-12xy= | | 1/2x-3=14/5-3/4x | | 17f^2+7f=0 | | 2=0.6x^2+3x+4 | | 12x-10=12-4x | | u-3+10u+6=102 | | 0=0.6x^2+3x+6 |

Equations solver categories